Could comorbid bipolar disorder account for a significant share of executive function deficits in adults with attention‐deficit hyperactivity disorder?. (29th November 2013) - Silva, Katiane L; Rovaris, Diego L; Guimarães‐da‐Silva, Paula O; Victor, Marcelo M; Salgado, Carlos AI; Vitola, Eduardo S; Contini, Verônica; Bertuzzi, Guilherme; Picon, Felipe A; Karam, Rafael G; Belmonte‐de‐Abreu, Paulo; Rohde, Luis A; et al.
<x xml:space="preserve">Abstract</x> Objective The frequent comorbidity between attention‐deficit hyperactivity disorder (ADHD) and bipolar disorder (BD) represents a challenge for disentangling specific impairments of each disorder in adulthood. Their functional impairments seem to be mediated by executive function deficits. However, little is known about the extent to which each executive function deficit might be disorder specific or explained by the comorbidity. The aim of the present study was to determine if comorbid BD could account for a significant share of executive function deficits when measured by the Wisconsin Card Sorting Test (WCST) in adults with ADHD. Methods Adult patients with ADHD and healthy subjects were evaluated in the ADHD outpatient Program at the Hospital de Clínicas de Porto Alegre. Psychiatric diagnoses were based on DSM‐IV criteria. WCST scores were compared by multivariate analysis of covariance among three groups: ADHD with BD (n = 51), ADHD without BD (n = 278), and healthy subjects (n = 91). Results When compared to patients without BD and healthy subjects, patients with ADHD and comorbid BD showed lower scores in total correct answers (p = 0.003); higher scores in total errors (p = 0.004) and non‐perseverative errors (p = 0.002); and completed fewer categories (p = 0.009). Patients with ADHD without BD did not differ from healthy subjects. Conclusions WCST impairments among patients with ADHD seem to be to a large extent attributable to comorbid BD. Although other executive function deficits (e.g., in the inhibitory control domain) have been demonstrated to accompany ADHD, the present findings suggest that set‐shifting deficits are strongly related to comorbid BD.